Kemampuan IT Guru di MGMP IPS Kabupaten Belitung Timur pada Pembuatan Website Pembelajaran Interaktif Tahun Pelajaran 2022/2023 - Sumiati Sumiati; Sukadari Sukadari (Proceedings Series on Social Sciences & Humanities, 2023)
Teachers as the main role holders in learning are required to have competencies that are in line with learning objectives. These competencies include pedagogic competence, personal competence, social competence and professional competence. The importance of teacher professionalism will be one of the determining factors for a quality education process because teachers should master and utilize various resources to support learning including mastering science, information and communication technology in accordance with the times. Technology is the result of the development of science, which was born from the world of education itself. Therefore, it is appropriate for education to utilize technology to assist the implementation of learning. In technology-based learning activities, teachers can create even develop an interactive learning media for creating an educative interactive learning’s atmosphere between teachers and students, students and students, as well as students with the environment as a source of learning to support the achievement of learning objectives. Teachers must always think more creative such as how to collaborate an innovating learning media that will be given to students, namely by using interactive learning media or digital multimedia-based. The learning website as an example of interactive learning media is a web-based learning media that can be used as a support for the learning process. However, to create these learning websites, teachers are often constrained by their limited ability to apply ICT. Mastery of computers and the internet in the learning process is still not optimal so that it affects the competence of teachers in applying ICT to create interactive learning media.